Metodologia para concepção de cabines de máquinas agrícolas com enfoque na segurança e ergonomia - Baumhardt, Ulisses Benedetti (2012)
In today's technological evolution process of agricultural machinery cabins, driven largely by precision agriculture, there is the existence of failures in the provision of safety and ergonomics. So how new technologies are being made available to the user in operation station as well as the ambience involved, become important factors to be worked out. In this sense, this thesis aimed to develop a methodology and tools for the insertion of such aspects in the project as well as evaluation of these application in a case study, referring to the cabin design of a selfpropelled sprayer. Among the methodologies that guided the proposed method are intended the safety (ALONÇO, 2004), ergonomics (IIDA, 2005), the project of agricultural machinery (ROMANO, 2003) and modular systems (MARIBONDO, 2000). In the results of this study, emphasized by the presentation of a methodology and software that included the phases of planning, project informational and conceptual as well as virtual tools directed to assist in the dimensioning of the cabin and its components. In application of the methodology proposed in cabin project of a self-propelled sprayer, with conducting research on standards and related material, we identified 60 security restrictions concerning the cabins in general and through the ergonomic analysis as well as data collected from users of the product, such information was processed resulting in 60 technical specifications of the product. Posteriorly, were characterized 35 elementary functions to the cabin, which, through the choice of the principles of solutions, originated three variants for the design, one of these being judged like that best met the technical specifications mentioned. Finally, it was found that the use of the proposed methodology and tools developed contributed to the identification and detailment of information to be considered in the project of cabins, respecting the principles of safety and ergonomics.